The Vietnamese nationals and their economic activities in Puerto Princesa City, Palawan (1975-2005). - Pueyo, Jemelette De Guzman
The study is entitled The Vietnamese Nationals and Their Economic Activities in Puerto Princesa City, Palawan (1975 to 2005). The study aimed to examine the existence of the Vietnamese nationals in the city. The study also discussed the different contributions of their economic activities to the city., The study aimed: 1. to find out the nature of the arrival of the Vietnamese nationals in Puerto Princesa City; 2. To describe the social, religious, and economic lives of the Vietnamese nationals the city ; 3. To describe the different economic activities of the Vietnamese nationals from the time they arrived in Puerto City up to the year 2005 and to determine how these economic activities started; 4. To determine the different strategies that the Vietnamese nationals had employed to gain partners and customers in Puerto Princesa City and the factors that motivate the existence of the Vietnamese economic activities until the present; 5. To find out the problems that the Vietnamese nationals had encountered in their economic activities and the solutions they applied; and 6. To examine the contributions of the economic activities of the Vietnamese nationals in Puerto Princesa City. The researcher employed oral history and interviews as the primary method in gathering data. Actual observation was also utilized in observing the different economic activities. Additional facts and data were gathered from library research and from the different institution that had records concerning the Vietnamese nationals. Moreover, photo documentation was utilized to exhibit the lives of the Vietnamese nationals in the city.The study found out that the Vietnamese nationals started to arrive in the country as early as the year 1975 through boats and airplanes. The Vietnamese nationals in Puerto Princesa City stayed either inside or outside the Viet Village and the Center for Assistance to Displace Persons (CADP) was responsible for them. Inside the village they had the Catholic Church, Evangelical Church, and Buddhist Temple and they celebrated several religious celebration. They also engaged in different economic activities such as rice noodle manufacturing, "chaolongan," french bread bakery, "hulugan," handicraft making, merchandising and retail store. Through being friendly and learning to speak Tagalog they were able to attract customers, however, sometimes customers were the primary problem of the some of the Vietnamese nationals, particularly those engaged in "hulugan." The other problems they encountered were high taxes and space rental. They usually let these problems passed because of their status in the country - they were not permanent residents. On the other hand, their economic activities had different contributions in the city in terms of taxes, tourism, employment, business opportunity to some Filipinos and warm relationship between the Vietnamese nationals and the Filipinos.